If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(-2y + -3 + 4n) = 0 Reorder the terms: -5(-3 + 4n + -2y) = 0 (-3 * -5 + 4n * -5 + -2y * -5) = 0 (15 + -20n + 10y) = 0 Solving 15 + -20n + 10y = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -20n + -15 + 10y = 0 + -15 Reorder the terms: 15 + -15 + -20n + 10y = 0 + -15 Combine like terms: 15 + -15 = 0 0 + -20n + 10y = 0 + -15 -20n + 10y = 0 + -15 Combine like terms: 0 + -15 = -15 -20n + 10y = -15 Add '-10y' to each side of the equation. -20n + 10y + -10y = -15 + -10y Combine like terms: 10y + -10y = 0 -20n + 0 = -15 + -10y -20n = -15 + -10y Divide each side by '-20'. n = 0.75 + 0.5y Simplifying n = 0.75 + 0.5y
| 2(x-1)+6x=4(-4x-1)+2 | | 2(x-1)+6x=4(-6-1)+2 | | 2(5x+4)=5x-3 | | 270=2.7x | | graphy=-x-4 | | 2(x-1)+6x=4(6-1)+2 | | 7+4q=12+3q | | 2(x-1)+6x=4(4-1)+2 | | 3-(x-5)=7(x+2) | | x+53+70+65=180 | | -10.9+0.5=0.9p+5.3 | | 8(x+2)+3x-5=10x-3(2x-1) | | 10+4=2(5z+8)-12 | | 4(x+6)+7(2x-4)=148 | | 0.5(4x+6)-8=-3x+5(x-2) | | 6x-7+2(4x-5)= | | 10x+18=x+4 | | 3a+b=7 | | 5x^2+12x+5=0 | | 5x+7=5x | | 21x-6=19x-12 | | -22-(-12)= | | 4e-12=-34 | | -4x=8y+10 | | 10+11= | | 4f+7=5f-(1+f) | | 4e=12 | | 1x=60 | | x^2+8x=-15x | | [c-3]=1 | | 6x-4=2(3x+7) | | 7(2p+1)=14p+1 |